Impact of mulching treatments on growth, yields, and economics of common bean (Phaseolus vulgaris L.) in Eastern Tanzania - Ramadhani, Ahamed Mwarabu; Nassary, Eliakira Kisetu; Rwehumbiza, Filbert B.; Massawe, Boniface H. J.; Nchimbi-Msolla, Susan (Frontiers in Sustainable Food Systems, 2024)
Mulching is a widely-used agricultural practice that can significantly affect crop growth, yield, and economic outcomes, particularly in regions with varying climatic conditions. The present study evaluated the influence of various mulching practices on the growth, yield, and economic viability of common bean (Phaseolus vulgaris L.) cultivation in Tanzania. Across three sites in eastern agro-ecological zone, including Kipera (E4 200-1000 m.a.s.l.), Mgeta (E14 500-2000 m.a.s.l.), and Ndole (E2 500-1200 m.a.s.l.), four mulching treatmentspolythene mulch, synthetic biodegradable mulch, rice husk mulch, and a control groupwere applied to assess their effects on plant growth and yield components. Results revealed significant variations in growth parameters and yield components across sites. Notably, polythene mulch and synthetic biodegradable mulch consistently outperformed others, with polythene mulch resulting in an average plant height of 68.37 cm and synthetic biodegradable mulch at 68.26 cm, significantly (p < 0.05) taller than rice husk mulch (62.79 cm) and the control (57.74 cm). Similarly, these mulches led to increased ground coverage, with polythene mulch resulting in the highest canopy cover at 61.7%, followed closely by synthetic biodegradable mulch at 60.5%. Grain yields did not differ significantly between synthetic biodegradable mulch (2.64 t ha -1 ) and polythene mulch (2.67 t ha -1 ). Economic analysis indicated promising marginal returns and benefit-cost ratios for synthetic biodegradable mulch, with a marginal return (MR) of Tshs. 3,787,450 or USD 1,469) and a benefit-cost ratio (BCR) of 1.91, compared to polythene mulch (MR: Tshs 4,114,050 or USD 1,595, BCR: 2.06). These findings highlight the potential of synthetic biodegradable mulch as a sustainable and economically viable option for enhancing common bean production in diverse agro-ecological settings.